Outdoor cultures of Chlorella pyrenoidosa in the effluent of anaerobically digested activated sludge: The effects of pH and free ammonia. (January 2016) - Tan, Xiao-Bo; Zhang, Ya-Lei; Yang, Li-Bin; Chu, Hua-Qiang; Guo, Jun
Highlights: Successful culture of C. pyrenoidosa in the diluted ADAS in outdoors. A high pH coupling with free ammonia toxicity actually inhabited the algal growth. A high pH brought in advantages for reducing contamination and improving lipids content. Abstract: A freshwater algae Chlorella pyrenoidosa was cultured outdoors using anaerobically digested activated sludge effluent. The effects of pH variations were evaluated. The coupled pH variations and free ammonia toxicity significantly affected the algal growth, lipids accumulation and contamination control during every season. The free ammonia toxicity at high pH levels actually inhibited the algal growth. Compared to an optimal algal growth at a pH of 5.7–6.5, biomass productivity at a high pH of 8.3–8.8 was reduced by 67.15 ± 6.98%, 54.39 ± 6.42% and 83.63 ± 5.71% in the spring, fall and summer, respectively. When the pH rose above 9.1–9.6, algae were unable to grow in the wastewater. However, high pH levels reduced contamination (e.g., bacteria and microalgae grazers) and triggered lipids accumulation in algal cells. These findings suggest that pH control strategies are essential for this type of algal wastewater system, where ammonia is the dominant nitrogen source.